Kilka tez o instrumentalizacji prawa i ochronie przed nią - Wronkowska, Sławomira (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Using the concept of instrumentalisation of law developed in Polish jurisprudence, the author of the article: — points out that the instrumentalisation of law can be attributed to various entities: the legislator, those interpreting the provisions of law, those applying the legal norms as well as the authors of the legal doctrine; — distinguishes forms of instrumentalisation by each of these entities; — points to dysfunctional acts of instrumentalisation; — demonstrates some mechanisms counteracting the instrumentalisation of law, mechanisms that are to be found in the very concept of law as developed in Western culture
Keywords: polityka; prawo; teoria prawa